Ventricular Septal Defect as a Complication of Blunt Chest Trauma: A Rare Occurrence and First Case-Report in Bangladesh - Chowdhury, AW; Reza, AQM; Baqui, MA; Muttalib, MA; Tanveer, MS; Islam, SA; Ullah, MS; Mondal, DK; Islam, SS; Shahidullah, MS; et al. (Cardiovascular Journal, 2011)
Traumatic ventricular septal defect (VSD) is a very uncommon condition, especially in association with blunt chest trauma. A healthy young adult was diagnosed as a case of VSD one week after a road-traffic accident. History and other medical records suggest it was an acquired post-traumatic VSD. Thus, all patients of blunt chest trauma deserve close cardiac evaluation. Key words: Ventricular septal defect, Blunt chest trauma. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8207 Cardiovasc. j. 2008; 1(1) : 105-108